Sosialisasi dan Pelatihan Pemilahan Sampah melalui Program Bank Sampah sebagai Upaya Pemberdayaan Masyarakat di Desa Jagabaya Kabupaten Lebak - Muara Torang Hadomuan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Waste management remains a serious environmental challenge in various regions, including Jagabaya Village, Lebak Regency. Low public awareness of waste sorting at the source and suboptimal waste bank management have led to increased waste generation, which impacts the environment and health. This community service activity aims to increase public knowledge, awareness, and participation in waste sorting and waste bank management. The implementation method uses an educational and participatory Participatory Action Research (PAR) approach, through a series of outreach, training, and mentoring. The activity involves village officials and the community as the primary subjects in formulating waste management problems and solutions according to the local context. The results of the activity show a significant increase in community understanding of waste types, their impacts, and the benefits of waste sorting and waste banks. There has also been increased active participation in sorting practices and a shared commitment between the community and the village government for sustainable waste management. Thus, this activity makes a strategic contribution to supporting the realization of a clean, healthy, and sustainable village environment in Jagabaya Village.